Neuromuscular paralysis caused by an overdose of emepronium bromide (Cetiprin). Issue 2 (June 1985) - Ferguson, A; Baker, D A
Abstract : Emepronium bromide (Cetiprin) is an anticholinergic agent used therapeutically to reduce urinary frequency. We describe a voluntary overdose, which caused respiratory failure due to neuromuscular paralysis.